Incidencia de los riesgos mecánicos de la EMMAP-EP en la seguridad y salud ocupacional de los(as) trabajadores(as) - Cedeño Alcívar, Anny Carolina (2021)
The present research aimed to evaluate the incidence of mechanical risks of the Municipal Public Jointed Drinking Water (EMMAP-EP) in the occupational health and safety of workers. The mechanical risks of the productive activities of the EMMAP-EP were identified. Subsequently, the risk assessment was carried out, and an occupational health and safety plan was proposed for the company. With the matrix of the Ministry of Labor Relations of Ecuador, and the method of William Fine (1971), the degree of danger of each identified risk was calculated based on the probability of occurrence, the consequences and the exposure to this risk. Eleven mechanical risks were identified in the productive activities of the company, of which 2 were identified with a high degree of danger and low impact, 16 with a medium degree of danger and low impact, and 22 with a degree of danger and low impact. An Occupational Health and Safety Plan was proposed that will allow to minimize the mechanical risk factors in the company, through the execution of the seven corrective measures proposed, such as the provision of PPE, implementation of an adequate signaling system, training for personnel of the productive area, cleaning and maintenance of the facilities and infrastructures, implementation of a first aid kit, and the performance of medical check-ups to the workers that allow safeguarding the safety and health of the workers during the performance of their duties.